The Impact of Missed Red Reflex Screening on Binocular Vision Outcomes in a Child with Bilateral Congenital Cataracts - Fadliyani, Eka; Sari, Munita; Imelda, Eva; Anggreiny, Cut Dini; Toshnowal, Nikhil (Heca Sentra Analitika, 2025)
Delayed recognition of congenital cataracts during the critical period of visual development can result in permanent neurovisual deficits. This case report describes a 5-year-old child with bilateral congenital cataracts who presented late with alternating exotropia. Ocular evaluation showed bilateral cataracts, alternating fixation on cover testing, and absent stereopsis, indicating long-standing visual deprivation. Despite cataract extraction, binocular function remained poor due to disruption of cortical binocularity beyond the sensitive developmental window. This case underscores the irreversible impact of late intervention and highlights the need for strengthened neonatal red reflex screening and timely referral to prevent avoidable lifelong visual impairment.